Il QT8 alle Triennali, l’esposizione di un cantiere in divenire: “mostrare” come atto esplicativo e formativo - Mauri, Margherita (Lo sguardo rinnovato, 2026)
The paper aims to analyze the ways in which the T8 district in Milan, created since the VIII Triennale of 1947, meets the definition of “experimental exhibition of modern architecture”. In a twofold sense: not only because architecture hosts and dialogues with different art forms, but because it itself becomes an object of exhibition: an “exhibition in the making,” unfolding over the years in parallel with the completion of the project, where the exhibition of form is also an exhibition of content, and the putting on display becomes an opportunity to educate and prepare the public (“It is indispensable that architects exert an influence on public opinion and make it aware of the means and resources of the new architecture,” Le Corbusier stated during the IV CIAM) for a new way of understanding and perceiving the urban and visual dimension.